A lightweight privacy-preserving data aggregation scheme with provable security for internet-of-things. Issue 3 (2nd April 2020) - Ogundoyin, Sunday Oyinlola
Abstract : In this work, an autonomous lightweight certificateless aggregate signature-based data aggregation scheme for internet-of-things (IoT) is proposed. In the scheme, IoT terminals only need to contact the key generation center (KGC) once. Subsequently, they can generate their pseudonyms on their own without any interaction with the KGC. An efficient revocation mechanism is provided to punish malicious terminals. The proposed scheme is anonymous, can provide conditional traceability, resist various attacks, and solves private key compromise problem. The formal security proof demonstrates that the scheme is secure against both Type I and Type II adversaries in the random oracle model based on the intractability of the Discrete Logarithm Problem. The performance evaluation shows that the proposed scheme is more efficient than the state-of-the-art schemes and fits the resource-constraint IoT environment.